PERSPEKTIF GURU PAI TERHADAP PENTINGNYA PEMBELAJARAN AKIDAH AKHLAK (Studi pada SD Negeri 14 Parepare) - Nursahrianti, Nursahrianti (JURNAL AL-QAYYIMAH, 2022)
This study aims to determine the PAI teacher's perspective on the importance of learning Akhlak at SD Negeri 14 Parepare. learning aqidah morals is one of the materials for Islamic education at SD Negeri 14 Parepare. However, in this case, it is necessary to have an important role in fostering students as a source and motivator in terms of goodness. Moral aqidah should be able to make students better, however whether the impact of the learning can shape the character of students as expected. The data collection method in this research is using qualitative research with a descriptive approach. The data sources used are Primary and Secondary data. The data collection technique is interviews (interviews) in order to obtain information in this study. The results of the study show that: (1) the role of a PAI teacher in learning the moral creed is of course very active because it provides the basics of moral aqidah where students are fostered and overcome bad behavior by providing motivation and making students the nation's generation who are not easily influenced by the world that is temporary, eternal in the Hereafter. So a PAI teacher plays an important role in shaping the character of students so that the realization of pious and pious students. (2) Islamic religious learning in the form of devotion to morals of faith has a very good impact in fostering students towards religious values such as being moral so that students are able to practice good morals and try their best to leave bad morals, both in relation to Allah SWT, themselves , between humans and their relationship with the environment. Likewise, students can also add knowledge, appreciation and great belief in things that must be observed, so that students can behave and behave daily based on the Qur'an and hadith. The moral creed teaches to increase belief in the one and only Allah SWT who never sleeps and does not have children, believing in Allah SWT is one of the first pillars of faith. So the impact on students can shape the character to become a person with noble character.